THE IMPACT OF ARTIFICIAL INTELLIGENCE - Mahmudova Sabina (“SUN’IY INTELLEKTNING TIL O‘RGANISHDAGI O‘RNI” MAVZUSIDA TALABALAR ILMIY-AMALIY KONFERENSIYASI, 2025)
This thesis examines the significant impact of Artificial Intelligence (AI) on various sectors of modern society. It discusses how AI technologies are reshaping the economy, labor market, education , healthcare, and ethical standards. While AI brings numerous benefits such as increased efficiency and innovation, it also presents challenges like job displacement, privacy concerns, and ethical dilemmas. The research highlights the importance of responsible AI development and the need for regulatory frameworks.